"So What's It About? Your Book, I Mean?". Issue 4 (28th November 2012) - Heath, Shirley Brice
Abstract While doubts surround relations between adolescents and books, Heath argues that today's adolescents seek out reading opportunities that develop and deepen their special interests. Wanting to know and do more than their parents, young people prize learning on their own time to advance skills, ways of knowing, and peer relationships. Doing so, they want to take every advantage that technologies give them. In doing so, they have to interpret numerous genres, visual images, and layered meanings. Based on three decades of research on the learning lives of working‐class families, Heath asserts the vital need for adults to learn about the special interests of today's adolescents and to develop with them joint projects and explorations of multiple sources of information both through the internet and in place‐based and face‐to‐face community resources such as museums and local experts.